COATING OF GUAVA (PSIDIUM GUAJAVA L.) FRUITS WITH BOTANICAL EDIBLE OILS FOR SHELF LIFE AND FRUIT FLIES - NAWAL A. ABDELRAHMAN, ESAMELDIN B. M. KABBASHI; MODATHIR, MOHAMED; SIYAM, AWAD S. A. (Food Biology, 2018)
Guava (Psidium guajava L.) fruit is a popular nutritious dessert in Sudan. It is famous for its medicinal values as a prompt cure for digestive disorders and respiratory ailness this besides being a rich source of C vitamin. This fruit is highly amenable to fruit fly attack and it is a harbor of eggs of five different species [Ceratitis capitata Wied.; Ceratitis quinaria Bez.; Ceratitis cosyra Wlk.; Bactrocera invadens De Trusta and White and Bactrocera zonata (Saunders)] in Sudan. This is stimulating to a chain of endless research to combat these notorious pests which account for huge losses in this crop that reach up to 80% or even more. This research aimed at evaluating the effect of oil coating on fruit fly infestation and the quality indexes in guava fruit using five different botanical edible oils. The results showed that groundnut (Arachis hypogaea L.) (GNO), sesame (Sesamum indicum L.) (SO), baobab (Adansonia digitata L.) (BO), olive (Olea europaea L.) (OO) and neem (Azadirachta indica A. Juss) (NO) oils effected a corrected disinfestation of 80, 72, 56, 52 and 28% in test fruits brought from Kadaro orchards North Khartoum, respectively. The corresponding average readings of maggots in infested fruits were 4, 17, 11, 5, 7 and [10 (for the first 4) and 26 for NO] in the control. Two essential quality indexes were checked in test fruits which included fruit color (FC) and firmness (FF). The corrected test readings reflected 64, 80, 44, 52,-4 and [8 (for the first 4) and 20 for NO] in the control sustained FC for GNO, SO, BO, OO, NO and the control, respectively. However, the corresponding readings for FF were 3 (medium) for all oils and 4 (soft) for the controls. These results reflect a potent and the best efficacy of peanut and sesame oils, of the five test oils, in controlling fruit flies in guava and extending its shelf life.